2015
DOI: 10.1016/j.rchipe.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Rabdomiólisis grave secundaria a deshidratación hipernatrémica

Abstract: Severe hypernatraemia is described as a rare cause of rhabdomyolysis and renal failure. In critically ill patients, it is important to have a high index of suspicion for rhabdomyolysis and performing serial determinations of creatine phosphokinase for early detection and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Hypernatremia means a plasma sodium concentration of more than 145 mmol/L 9 . The hypertonic state caused by hypernatremia also has a tremendous impact on the organism, and the deleterious effects of this hypertonic state on patients include brain cell shrinkage, cerebral demyelination, coma, rhabdomyolysis and reduced left ventricular function 10 and rhabdomyolysis 11,12 . The development of hypernatremia in COVID‐19 patients is usually due to fever, diarrhea, anorexia, and decreased fluid intake, 13 in addition, studies have shown that advanced age, dementia, and institutionalization are important risk factors for the development of hypernatremia in patients with COVID‐19 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypernatremia means a plasma sodium concentration of more than 145 mmol/L 9 . The hypertonic state caused by hypernatremia also has a tremendous impact on the organism, and the deleterious effects of this hypertonic state on patients include brain cell shrinkage, cerebral demyelination, coma, rhabdomyolysis and reduced left ventricular function 10 and rhabdomyolysis 11,12 . The development of hypernatremia in COVID‐19 patients is usually due to fever, diarrhea, anorexia, and decreased fluid intake, 13 in addition, studies have shown that advanced age, dementia, and institutionalization are important risk factors for the development of hypernatremia in patients with COVID‐19 14 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 The hypertonic state caused by hypernatremia also has a tremendous impact on the organism, and the deleterious effects of this hypertonic state on patients include brain cell shrinkage, cerebral demyelination, coma, rhabdomyolysis and reduced left ventricular function 10 and rhabdomyolysis. 11 , 12 The development of hypernatremia in COVID‐19 patients is usually due to fever, diarrhea, anorexia, and decreased fluid intake, 13 in addition, studies have shown that advanced age, dementia, and institutionalization are important risk factors for the development of hypernatremia in patients with COVID‐19. 14 Recent research indicates that the prevalence of hypernatremia in patients with COVID‐19 is between 2% and 7% and is associated with the risk of death in patients with COVID‐19, 6 , 7 , 8 , 15 , 16 this suggests that hypernatremia is associated with mortality risk in patients with COVID‐19.…”
Section: Introductionmentioning
confidence: 99%